The association of methylglyoxal-adducts with kinetics and ultrastructure of fibrin clots in coronary artery disease patients with type 2 diabetes mellitus - Phulukdaree, Alisa (University of Pretoria, 2021)
Dissertation (MSc (Physiology))--University of Pretoria, 2020.